PENGARUH KINERJA TUTOR DALAM PEMBELAJARAN TERHADAP PRESTASI BELAJAR WARGA BELAJAR T.A 2020/2021 DI SATUAN PENDIDIKAN NON FORMAL (SPNF) SANGGAR KEGIATAN BELAJAR (SKB) KOTA PEKANBARU - Ananda, Juria Tri; Wilson, Wilson; Natuna, Daeng Ayub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the effect of tutor's performance in learning on the learning achievement of residents learning the learning activity studio (SKB) Pekanbaru City. The formulation of the problem in this research is how high is the performance of tutors in the Non-Formal Education Unit (SPNF) of the Pekanbaru City Learning Activity Center (SKB)? This study consists of 2 variables, namely the Tutor Performance variable (X) and the Learning Achievement variable (Y), where the Tutor Performance variable (X) has 4 indicators and the Learning Achievement variable (Y) uses the measurement of the average value of the student report cards for the 2020 academic year. /2021. The population in this writing is the learning community of the Pekanbaru City Learning Activity Center (SKB) as many as 103 learning residents. The sampling technique with stratified random sampling used was proportionate stratified random sampling, which is a sampling technique that if the population has heterogeneous members or elements and has proportional strata, totaling 42 statements for the variable tutor performance, totaling 51 people for the research sample. After the questionnaire was tested, there were 5 invalid statements on the tutor's performance variable, and discarded invalid statements. Based on descriptive analysis based on variables, it is obtained that the performance level of tutors in the environment around the Learning Activity Center (SKB) with a mean of 4.03 which is in a high interpretation. Based on the descriptive based on the existing learning achievement variable owned by the learning community members of the Learning Activity Center (SKB) with a mean of 81.17 which is in the high interpretation. A significant influence was obtained between the Tutor's performance variable on the learning achievement of the learning achievement of the Pekanbaru City Learning Activity Studio (SKB), which had a large effect of 12.3% with a low interpretation, because there were still 87.7% determined by other factors that were not part of the writing. this.Key Words: Tutor Performance, Learning Achievement, Learning Citizens